TEMPORALITAS PADA VERBA DALAM BAHASA DANI BARAT - Supardi, Supardi (LITERA, 2016)
This study aims to describe the temporality aspect of verbs in the Western Dani Language (WDL) in Papua. The data were from Morfologi Bahasa Dani Barat, a research report by Purba, et al. (1994). The temporality was proved by the distributional method supplemented by permutation and deletion techniques. The findings show that WDL has nine verb forms. Those are ones with: 1) a singular subject for the present tense, 2) a singular subject for the recent past tense, 3) a singular subject for the remote past tense, 4) a singular subject for the future tense, 5) a plural subject for the present tense, 6) a plural subject for the recent past tense, 7) a plural subject for the remote past tense, 8) a plural subject for the future tense, and 9) the habitual present tense. Temporality verb forms are classified into two groups: eight verbs based on the time an event occurs and one verb of a habitual event. The nine verbs showing time are distinguished on the basis of singular and plural subjects.